The role of chalcogen vacancies for atomic defect emission in MoS2 - Elmar Mitterreiter (Nature Portfolio, 2021)
The relation between the microscopic structure and the optical properties of atomic defects in 2D semiconductors is still debated. Here, the authors correlate different fabrication processes, optical spectroscopy and electron microscopy to identify the optical signatures of chalcogen vacancies in monolayer MoS2.